Analysis of factors influencing reported housing maintenance costs in Sweden’s public and private rental sectors - Muyingo, Henry Gonza (International Journal of Strategic Property Management, 2017)
The reported maintenance costs per unit area within the public rental housing sector in Sweden are consistently higher than those within the private rental sector. This paper uses crosssectional panel data analysis as well as a questionnaire survey sent to 196 managers in the private and public housing sectors to identify the factors that might explain this divergence. The findings indicate that “fundamental” factors such as the age of the houses or the composition of the tenants cannot explain the observed difference. However how the activities are classified and the timing of the measures are factors that can. The conclusions from the study are that the public companies should act more as the private sector in their accounting; wait longer than they currently do before carrying out some renovations; and that they should be more stringent when determining the resources to spend on large-scale maintenance and/or renovation projects.